Fiscal outcomes in Bahrain: Oil price volatility, fiscal institutions or politics? - El-Enbaby, Hoda; Selim, Hoda (Economic Research Forum, 2018)
The paper argues that political economy factors, rather than oil wealth, shape the budgetary process and outcomes in Bahrain. Fiscal volatility and excessive current spending (in the form of wages, social welfare and subsidies) leading to unsustainable non-oil deficits are not fully derived from oil price volatility. Weak institutions including those underlying the budgetary process contributed to some fiscal laxity. They have allowed rulers to use current spending as a channel for the redistribution of oil rents and to secure political stability and allegiance to the regime in a turbulent socio-political environment. The budgetary process is undermined by the structure of the bicameral parliament and the absence of restrictions on the parliament to amend the budget weaken the position of the executive. In the general context of limited transparency and accountability, the government may also be exercising its discretionary powers over the budget execution but it would not be known.